Shaving and shortening the hair during Hajj and Umrah: Jurisprudential study - aleidan, Haya bint Mohammed bin Fahd bin Sultan (Tobruk University Journal of Social and Human Sciences, 2025)
I used the inductive deductive approach in this research, as well as I discussed the  difference between shaving and shortening and their detailed rulings in Hajj and Umrah in terms of whether they are part of the rituals or a forbidden release, and the sufficient rate for women and men, as well as the ruling of the bald who has no hair, and their time in Hajj and Umrah, as well as their place., and the order of shaving and shortening works of the day of sacrifice, and then I identified the effects of shaving and shortening the first and second Tahalul, and after that I concluded the research with the most important results and recommendations, the most important of which are: they are rituals in Hajj, and they include two duties, servitude to Allah, and shortening for a man does not have a specific limit, unlike a woman, it is the amount of a fingertip, to other listed results